2019
DOI: 10.1038/s41598-019-39559-7
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein mimics insulin action on autophagy and glucose uptake in endothelial cells

Abstract: Elevated plasma low density lipoprotein (LDL) is an established risk factor for cardiovascular disease. In addition to being able to cross the endothelial barrier to become accumulated in subendothelial space and thereby initiate atherosclerosis, LDL may exert a direct effect on vascular endothelial cells through activation of LDL receptor and its downstream signaling. Whether LDL can modulate the signaling for autophagy in endothelial cells is not clear. The present study firstly demonstrated that LDL can sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…GLUT-1 overexpression promotes the proliferation, invasion, and metastasis of cancer cells, particularly under hypoxia and starvation conditions [6,7]. Activation of autophagy promotes the functions of CD133 + cells under hypoxia [15,16], likely by enhancing glucose uptake [21][22][23]. Therefore, we explored whether the increased proliferation and migration of CD133 + Tu212 cells were associated with elevated GLUT-1 expression and autophagy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GLUT-1 overexpression promotes the proliferation, invasion, and metastasis of cancer cells, particularly under hypoxia and starvation conditions [6,7]. Activation of autophagy promotes the functions of CD133 + cells under hypoxia [15,16], likely by enhancing glucose uptake [21][22][23]. Therefore, we explored whether the increased proliferation and migration of CD133 + Tu212 cells were associated with elevated GLUT-1 expression and autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy modulates various metabolic pathways, including that centered on glucose [23]. Hypoxia and glucose deprivation may induce autophagy, promoting glucose uptake by upregulating GLUT-1 expression to increase the glycolytic ux and maintain nutrient uptake under stress conditions [21][22][23]40,41]. In airway progenitor cells, a lack of GLUT-1 impacts its recycling but not its expression, facilitating glucose uptake [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that GLUT-1 overexpression promoted cancer cell proliferation, invasion and metastasis, especially in hypoxia and starvation conditions [6,7]. Besides, activated autophagy promoted the functions of CD133 + cells under hypoxia [15,16], probably by enhancing cell glucose intake [21][22][23].…”
Section: The Expression Of Glut-1 and Cell Autophagy In Cd133 + Larynmentioning
confidence: 96%
“…MetS-induced autophagy dysregulation has been identified as a critical factor in endothelial dysfunction and atherosclerosis. LDL can suppress endothelial autophagy by activating the PI3K/Akt/mTOR pathway in ECs ( Zhu L. et al, 2019 ). In addition, ox-LDL can inhibit autophagic flux by suppressing the Sirtuin 1 (SIRT 1)/forkhead box protein O1 (FoxO1) pathway to promote apoptosis and adhesion molecule expression in ECs ( Wang et al, 2019 ; Wu Q. et al, 2019 ).…”
Section: Autophagy In Atherosclerosismentioning
confidence: 99%